BETWEEN FAITH AND LEGALITY: A STUDY ON THE REGULARIZATION OF PUBLIC LANDS OCCUPIED BY RELIGIOUS AND WELFARE ENTITIES IN THE FEDERAL DISTRICT - Dantas , Eulírio de Farias; Abreu, Charles Sarmento; Junior, Clarimar Santos Motta; Graim, Jamille Saraty Malveira; de Araújo, Ésio Vieira (Seven Editora, 2024)
The article explores the relationship between Church and State in Brazilian Constitutions, focusing on secularism and the growing political power of evangelicals. The research investigates how this influence impacts the regularization of public land occupied by religious and social assistance entities, which are objects of study in the Third Sector. Using a methodology that combines legal-constitutional analysis and the complex approach of Edgar Morin, the study highlights the historical construction of religious influence in Brazil. In the Federal District, urban expansion and population pressure complicate land regularization. Between 1991 and 2008, many legislative efforts failed due to violations of the Constitution and the LODF. Complementary Law No. 806/2009 and Law No. 6,888/2021 are important to resolve these issues, proposing new parameters for collaboration between the State and non-profit entities. The article's hypothesis, confirmed by statistical data, suggests that the increase in the political power of evangelicals influences the regularization of public land in the Federal District, evidencing a correlation between the growth of the evangelical population and the formulation of specific legislation. DOI:https://doi.org/10.56238/sevened2024.037-003